Generative and transformational techniques in software engineering III International Summer School, GTTSE 2009, Braga, Portugal, July 6-11, 2009. Revised Papers - GTTSE (Summer School) 2009 Braga, Portugal); Fernandes, João M.; Lämmel,Ralf.; Visser, Joost; Saraiva, João.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This tutorial book presents revised and extended lecture notes for a selection of the contributions presented at the International Summer School on Generative and Transformational Techniques in Software Engineering (GTTSE 2009), which was held in Braga, Portugal, in July 2009. The 16 articles comprise 7 long tutorials, 6 short tutorials and 3 participants contributions; they shed light on the generation and transformation of programs, data, models, metamodels, documentation, and entire software systems. The topics covered include software reverse and re-engineering, model driven engineering, automated software engineering, generic language technology, and software language engineering.
Introduction to Software Product Line Refactoring -- Excerpts from the TXL Cookbook -- Model Synchronization: Mappings, Tiles, and Categories -- An Introductory Tutorial on JastAdd Attribute Grammars -- Model Driven Language Engineering with Kermeta; EASY Meta-programming with Rascal -- The Theory and Practice of Modeling Language Design for Model-Based Software Engineering--A Personal Perspective -- Code Transformations for Embedded Reconfigurable Computing Architectures -- Model Transformation Chains and Model Management for End-to-End Performance Decision Support; Building Code Generators with Genesys: A Tutorial Introduction; The Need for Early Aspects -- Lightweight Language Processing in Kiama -- Some Issues in the Archaeology of Software Evolution; Teaching Computer Language Handling From Compiler Theory to Meta-modelling; C++ Metastring Library and Its Applications -- Language Convergence Infrastructure.
Electronic reproduction.
Keywords: Software engineering -- Congresses; Electronic books